2016
DOI: 10.1016/j.celrep.2016.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide 1 Receptor Signaling in Acinar Cells Causes Growth-Dependent Release of Pancreatic Enzymes

Abstract: Incretin-based therapies are widely used for type 2 diabetes and now also for obesity, but they are associated with elevated plasma levels of pancreatic enzymes and perhaps a modestly increased risk of acute pancreatitis. However, little is known about the effects of the incretin hormone glucagon-like peptide 1 (GLP-1) on the exocrine pancreas. Here, we identify GLP-1 receptors on pancreatic acini and analyze the impact of receptor activation in humans, rodents, isolated acini, and cell lines from the exocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…No further increase suggesting GLP-1-mediated increased constitutive release of enzymes nor subclinical pancreatitis was seen. 11 Therefore, our present observations might reflect hyperlipidaemia-associated pancreatic injury with increased lipase enzyme activity in obesity.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…No further increase suggesting GLP-1-mediated increased constitutive release of enzymes nor subclinical pancreatitis was seen. 11 Therefore, our present observations might reflect hyperlipidaemia-associated pancreatic injury with increased lipase enzyme activity in obesity.…”
Section: Discussionmentioning
confidence: 61%
“…In in vitro studies and animal models, GLP‐1 has been shown to increase beta‐cell mass through beta‐cell regeneration, proliferation, and neogenesis in immature islets, whereas fully differentiated adult human beta‐cells appear unable to proliferate, . Little is known about the effects of GLP‐1 on the exocrine pancreas, and its impact on the release of pancreatic lipase levels is controversially discussed …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common drug‐related AEs reported in the present study were gastrointestinal (eg, diarrhoea or nausea), which were transient and rarely led to treatment discontinuation. A similar pattern of pancreatic enzyme increase associated with dulaglutide and the GLP‐1RA class of drugs was also observed in the present study. Small elevations in the mean concentration of pancreatic enzymes within a normal range were observed over time.…”
Section: Discussionmentioning
confidence: 99%
“…"Clearly, the development of the first antagonists with (subtype) selectivity for EPAC represents another research milestone to ascribe biologic responses to EPAC" (915). Indeed, these selective EPAC2 inhibitors are becoming effective tools in probing isoform-specific EPAC functions (18,47,130,175,226,250,302,411,463,565,682,743,841,896,961,1114).…”
Section: B Epac Specific Antagonistsmentioning
confidence: 99%